Методи та засоби захисту від шкідливих виробничих факторів та контролю навколишнього природного середовища - Таран, А. Ю.; Хондак, І. І. (ХНУРЕ, 2025)
The main methods and means of protection against harmful production factors, as well as modern approaches to environmental control, are considered. The main types of harmful effects on workers and the environment are identified and methods for their minimization are proposed. Special attention is paid to collective and individual protection systems, as well as automated means of monitoring harmful factors.
Keywords: навколишнє середовище; захист від шкідливих факторів